2009
DOI: 10.1371/journal.pone.0005741
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Thermal Response Properties in a Cold-Activated TRP Channel

Abstract: Animals sense changes in ambient temperature irrespective of whether core body temperature is internally maintained (homeotherms) or subject to environmental variation (poikilotherms). Here we show that a cold-sensitive ion channel, TRPM8, displays dramatically different thermal activation ranges in frogs versus mammals or birds, consistent with variations in these species' cutaneous and core body temperatures. Thus, somatosensory receptors are not static through evolution, but show functional diversity reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 23 publications
3
77
0
Order By: Relevance
“…Because temperatures beyond the appropriate range have detrimental effects (32,33), the activation temperature threshold for xtTRPV1 may be lower than that of mammalian TRPV1, which is several degrees higher than the core body temperature. To support this, it is also reported that there are striking correlations between species core body temperatures and the temperature ranges that activate transient receptor potential melastatin 8 (TRPM8) (34). Therefore, thermal activation of TRPV1 may also be tuned to the most appropriate temperature ranges for respective species.…”
Section: Discussionmentioning
confidence: 96%
“…Because temperatures beyond the appropriate range have detrimental effects (32,33), the activation temperature threshold for xtTRPV1 may be lower than that of mammalian TRPV1, which is several degrees higher than the core body temperature. To support this, it is also reported that there are striking correlations between species core body temperatures and the temperature ranges that activate transient receptor potential melastatin 8 (TRPM8) (34). Therefore, thermal activation of TRPV1 may also be tuned to the most appropriate temperature ranges for respective species.…”
Section: Discussionmentioning
confidence: 96%
“…A similar approach revealed sites within the cold receptor, TRPM8 (35), that determine sensitivity to cooling compounds (36). Although this method has greatly facilitated the analysis of chemical sensitivity, it has met with limited success in delineating regions that account for thermal sensitivity because TRPV1 and TRPM8 from different species retain temperature sensitivity as a highly conserved function, save for differences in precise temperature activation threshold (34,37). Thus, cross-species chimeric channels cannot be used to transfer heat or cold sensitivity cleanly to a thermoinsensitive ortholog.…”
mentioning
confidence: 99%
“…Innate behavioral responses to temperature have probably evolved to match specific habitats and physiology. For example, the threshold for activation of the cold-sensitive ion channel TRPM8 correlates with core body temperature in vertebrates (Myers et al 2009). Genetic variations also modulate nociception and temperature sensation within species.…”
mentioning
confidence: 99%